ELECTROCHEMICAL INVESTIGATION ON THE FORMATION OF DY-FE ALLOY IN MOLTEN CHLORIDES - Guankun L.; Yexiang T.; Huichan H.; Qiqin Y.; Shengyang C.; Jinxi G. (My University, 1997)
The electrochemical behavior of Dy3+ on Fe electrode in molten NaCl-KCl-DyCl3 has been studied by means of cyclic voltammetry, electrode potential-time curve after potentiostatic electrolysis, potential-step method, and X-ray diffraction. Experimental results indicate that the Dy-Fe alloy forms at first and then the intermetallic compounds of Dy-Fe containing more Dy form in sequence. The metallic Dy deposits at last. The number of intermetallic compounds for Dy-Fe system has been determined at 1073 K. The standard free energy of formation for (1/2)Dy2Fe17, (1/6)Dy6Fe23, DyFe3, and DyFe2 determined are -92.64, 83.10, -76.99, and -59.05 kJ/ mol at 1073 K. The relationship between diffusion coefficient and temperature of Dy atom in DyFe intermetallic compound can be expressed as ln D = - 72.9 × 103/RT - 14.7, and the diffusion activation energy is 72.9 kJ/mol. The Dy-Fe alloy was prepared by consumable cathode in molten chlorides. The Dy-Fe alloy containing Dy near 90%(wt) was obtained. The composition of alloy was DyFe3 and Dy.